The effects of positive leadership on quality of work and life of family doctors: The moderated role of culture - Sun, Wei; Huang, Xianhong; Chen, Xingyu; Wu, Yan; Huang, Zhen; Pang, Yichen; Peng, Can; Zhang, Yunjie; Zhang, Hao (Frontiers in Psychology, 2023)
Background Quality of work and life (QWL) of family doctors is highly valued in improving access and equity of healthcare; however, the current low level of QWL in many countries and regions needs to be improved urgently. Methods This study explored the effect of positive leadership on the QWL of family doctors, as well as the moderating role of culture, via analysis of data from 473 valid questionnaires of family doctors in China as a sample using SEM, hierarchical linear regression, and a simple slope test. Results The empirical results show that positive leadership promoted the QWL of family doctors by improving their achievement motivation and coordinating supportive resources. In addition, our hierarchical linear regression analysis found that the interactive items of positive leadership and culture had a positive effect on achievement motivation (β(a) = 0.192), QWL (β(b) = 0.215) and supportive resources (β(c) = 0.195). Meanwhile, culture had a moderated mediating effect on the relationship between positive leadership and QWL via the achievement motivation of family doctors and supportive resources. Conclusion These findings suggest that the interaction among multiple factors, including environmental factors, individual physiological features and culture, may influence the impact of positive leadership on the QWL of family doctors. The possible reasons of these findings and theoretical and practical implications are discussed in this study.